Gene Expression of Leptin and Long Leptin Receptor Isoform in Endometriosis: A Case-Control Study - Andrea Prestes Nácul; Sheila Bunecker Lecke; Maria Isabel Edelweiss; Débora Martinho Morsch; Poli Mara Spritzer (Obstetrics and Gynecology International)
In this study, leptin/BMI ratio in serum and peritoneal fluid and gene expression of leptin and long form leptin receptor (OB-RL) were assessed in eutopic and ectopic endometria of women with endometriosis and controls. Increased serum leptin/BMI ratio was found in endometriosis patients. Leptin and OB-RL gene expression was significantly higher in ectopic versus eutopic endometrium of patients and controls. A positive, significant correlation was observed between leptin and OB-RL transcripts in ectopic endometria and also in eutopic endometria in endometriosis and control groups. A negative and significant correlation was found between OB-RL mRNA expression and peritoneal fluid leptin/BMI ratio only in endometriosis. These data suggest that, through a modulatory interaction with its active receptor, leptin might play a role in the development of endometrial implants.